Acetylsalicylic Acid and Mood Disorders: A Systematic Review - Monika Dominiak; Adam Gędek; Michalina Sikorska; Paweł Mierzejewski; Marcin Wojnar; Anna Z. Antosik-Wójcińska (MDPI AG, 2022)
The effects of acetylsalicylic acid (ASA) on mood disorders (MD) and on inflammatory parameters in preclinical and clinical studies have not yet been comprehensively evaluated. The aim of this study was to systematically summarize the available knowledge on this topic according to PRISMA guidelines. Data from preclinical and clinical studies were analyzed, considering the safety and efficacy of ASA in the treatment of MD and the correlation of inflammatory parameters with the effect of ASA treatment. Twenty-one studies were included. Both preclinical and clinical studies found evidence indicating the safety and efficacy of low-dose ASA in the treatment of all types of affective episodes in MD. Observational studies have indicated a reduced risk of all types of affective episodes in chronic low-dose ASA users (HR 0.92, 95% CI: 0.88, 0.95, p < 0.0001). An association between ASA response and inflammatory parameters was found in preclinical studies, but this was not confirmed in clinical trials. Further long-term clinical trials evaluating the safety and efficacy of ASA in recurrent MD, as well as assessing the linkage of ASA treatment with inflammatory phenotype and cytokines, are required. There is also a need for preclinical studies to understand the exact mechanism of action of ASA in MD.